Gain more for less : the surprising benefits of QoS management in constrained NDN networks - Cenk Gündogan; Jakob Pfender; Michael Frey; Thomas C. Schmidt; Felix Shzu-Juraschek; Matthias Wählisch (ACM Conference on Information-Centric Networking 2019, 2019)
Quality of Service (QoS) in the IP world mainly manages forwarding resources, i.e., link capacities and buffer spaces. In addition, Information Centric Networking (ICN) offers resource dimensions such as in-network caches and forwarding state. In constrained wireless networks, these resources are scarce with a potentially high impact due to lossy radio transmission. In this paper, we explore the two basic service qualities (i) prompt and (ii) reliable traffic forwarding for the case of NDN. The resources we take into account are forwarding and queuing priorities, as well as the utilization of caches and of forwarding state space. We treat QoS resources not only in isolation, but correlate their use on local nodes and between network members. Network-wide coordination is based on simple, predefined QoS code points. Our findings indicate that coordinated QoS management in ICN is more than the sum of its parts and exceeds the impact QoS can have in the IP world.
Keywords: Internet of Things; ICN; Quality of Service; measurement